Ocean atmospheric coupled model to estimate energy and path of cyclone near the coast - DATTA, RAMKRISHNA (MAUSAM, 2013)
;g ns[kk x;k gS fd caxky dh [kkM+h esa vf/kdka’kr% pØokr] gjhdsu vkfn tSlh ok;qeaMyh; ifj?kVuk,¡ viuh xfr ds nk¡bZ vksj c<+rh gSaA ,lh ?kVukvksa dk v/;;u djus ds fy, geus ok;qeaMyh; xfr ;qfXer] egklkxj dh rjy xfrdh; ij fopkj fd;k gSA bl v/;;u esa geus pØokrh; ra= ds dsUnz dks fy;k gS ftlesa rjy xfrdh; lzksr rFkk FkksMh lh nwjh ij rjy xfrdh; flad gksrk gSA bl izdkj fcEc ra= ds rjy xfrdh; f}d ¼MCysV½ fufeZr gksrk gSA rnqijkar fcEc rjax vkSj mlds izfrfcEc rjax ds rjy xfrdh; f}d ¼MCysV½ ij Bksl nhokj ¼;gk¡ ij leqanz dk fdukjk½ ds laca/k esa fopkj fd;k x;kA blesa fcEc ra=] izfrfcEc ra= vkSj /kkjk xfr ls lacaf/kr fefJr fcEc ds rjy xfrdh; lehdj.k ij dk;Z fd;k x;k gSA fcEc ra=] izfrfcEc f}d ¼MCysV½ rFkk /kkjk xfr ds fefJr foHko ij bl 'kks/k i= esa fopkj fd;k x;k gSA xfr lfn’k] QyLo:i nkc dks rjy xfr ds cjukSyh ds lehdj.k dh lgk;rk ls iqu% izkIr fd;k x;kA rnqijkar leqnz ds fdukjs vFkkZr~ nhokj ij U;wure@vf/kdre nkc dh fo’ys"k.kkRed x.kuk dh xbZA vr% ;g ns[kk x;k fd pØokr vFkok gjhdsu dh ekStwnk iou vkSj ÅtkZ dqN izpfyr fLFkfr;ksa ds vk/kkj ij leqnz rV dh vksj vFkok mldh xfr ds nk¡bZ vksj tkrh gSA It is seen that in the Bay of Bengal or in the Gulf, most of the time the atmospheric phenomena, like, cyclone, hurricane etc. move towards right to its motion. To study such occurrences; we have considered fluid dynamics of ocean coupled with atmospheric motion. In the present study we have considered the eye of the cyclonic system that consist of fluid dynamical source and fluid dynamical sink at a small distance apart, and thus, constitute the fluid dynamical doublet of the object system. Then the fluid dynamical doublet of the object system and its image system has been considered with respect to a firm wall (here the sea shore). The fluid dynamical equation of complex potential with respect to the object system, the image system and the stream velocity have been undertaken. The complex potential of the object doublet, image doublet and the stream velocity have been considered. The velocity vector, consequently the pressure has been retrieve with the help of Bernoulli’s equation of fluid motion. Then the minimum /maximum pressure on the wall that is on the sea shore has been calculated analytically. Thus, it is found that on the basis of some prevailing conditions existing wind and energy the cyclone or hurricane move towards the sea coast or to the right of its motion.